Developing Project-Based Learning Related to Local Wisdom in Improving Students’ Problem-Solving Skills - Rita Retnowati; Rita Istiana; Nadiroh Nadiroh (JETL (Journal of Education, Teaching and Learning), 2020)
The purpose of this research is to determine the effectiveness of the development of the Project-Based Learning (PjBL) model based on local wisdom in solving environmental problems and the students’ ability to develop learning media. Research conducted at Educational Faculty and teaching sciences of Pakuan University. This research uses the method of Research and Development with the ADDIE model, comprising analyses, design, development, implementation, and evaluation. The data were obtained from the validation by three experts, namely learning material expert, learning media expert, and learning model expert. The effectiveness assessment was done by N-Gain assessment environmental problem-solving ability and evaluating the multimedia product. The steps to develop the model are as follows: need analysis, designing learning model development, learning model development, learning model validation by the experts, learning model implementation in class, and model evaluation. The product created by the students from learning through PjBL based on local wisdom is a video about local wisdom. According to the data analysis result, it can be concluded that model development of PjBL based on local wisdom improves their ability to solve environmental problems, the average score is 0.69 in experiment class and the score in control class is 0.055 (scales of 0-1.0). The ability to develop video environmental learning media the score video product in experiment class is 2.4 and in the control class is 2.2 (scales of 1-3).